Circular RNAs regulate parental gene expression: A new direction for molecular oncology research - Wang, Haicun; Gao, Xin; Yu, Shaobo; Wang, Weina; Liu, Guanglin; Jiang, Xingming; Sun, Dongsheng (Frontiers in Oncology, 2022)
CircRNAs have been the focus of research in recent years. They are differentially expressed in various human tumors and can regulate oncogenes and tumor suppressor genes expression through various mechanisms. The diversity, stability, evolutionary conservatism and cell- or tissue-specific expression patterns of circRNAs also endow them with important regulatory roles in promoting or inhibiting tumor cells malignant biological behaviors progression. More interestingly, emerging studies also found that circRNAs can regulate not only other genes expression, but also their parental gene expression and thus influence tumors development. Apart from some conventional features, circRNAs have a certain specificity in the regulation of parental gene expression, with a higher proportion affecting parental gene transcription and easier translation into protein to regulate parental gene expression. CircRNAs are generally thought to be unable to produce proteins and therefore the protein-coding ability exhibited by circRNAs in regulating parental gene expression is unique and indicates that the regulatory effects of parental gene expression by circRNAs are not only a competitive binding relationship, but also a more complex molecular relationship between circRNAs and parental gene, which deserves further study. This review summarizes the molecular mechanisms of circRNAs regulating parental gene expression and their biological roles in tumorigenesis and development, aiming to provide new ideas for the clinical application of circRNAs in tumor-targeted therapy.